MANAJEMEN PENGUATAN SUMBER DAYA KARAKTER RELIGIUS SISWA DI SDS BAYT TAMYIZ SUKAPERNA - Hana Tadzkiya; Nurfuadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of religious character resource management at SDS Bayt Tamyiz Sukaperna. The research focuses on four management functions: planning, organizing, actuating, and controlling within the religious character strengthening program. A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students. The findings indicate that: (1) planning is grounded in the Al-Qur'an and As-Sunnah, involving all stakeholders; (2) organizing is implemented through role distribution among teachers, coordination with parents, and conditioning of an Islamic school culture; (3) actuating is realized through daily worship habituation, etiquette cultivation, teacher exemplary behavior, and character reinforcement programs such as Galaxy Akhlak and Bintang Akhlak; and (4) supervision is conducted through weekly and monthly evaluations, mutaba'ah-based monitoring, and continuous follow-up. The program has produced a significant positive impact on students' religious character development, reflected in worship consistency, Islamic etiquette, and daily behavior.